Using Religious Capital to Alleviate Poverty? - A Case Study of Cross-Border Migration in South-China (abstract) - Sam Wong (Revue Internationale de Politique de Développement)
Laurence Iannaccone’s notion of religious capital highlights the capability of individuals to draw on resources from religious- or faith-based practices, and then convert religious capital into human, social and financial capital. The processes of capital accumulation and conversion have significant implications for poverty reduction. However, in its examination of the cross-border experiences of poor female Chinese migrants in South China, this chapter finds that religious capital is severely inequitably distributed within migrant communities. Religious involvement is both time- and resource- demanding, and the very poor face considerable constraints in negotiating access to religious capital. Empirical evidence indicates that while some migrants are successful in improving their material conditions and experience upward social mobility, the failure to address broader, deep-rooted causes of poverty, such as social discrimination, has stymied more systemic change. Worse still, members of the ruling class use religious symbols and rituals to reinforce their domination. This chapter calls for placing greater emphasis on the distributional effect of religious capital, with the aim of offering poor people better support for their religious participation.